Mental health and dual sensory loss in older adults: a systematic review - Heine, Chyrisse; Browning, Colette J. (Frontiers in Aging Neuroscience, 2014)
Mental health is a core component of quality of life in old age. Dual Sensory Loss (DSL; combined vision and hearing loss) is prevalent in older adults and has been correlated with decreased levels of well-being. This systematic review aimed to critically review and summarize the evidence from studies that examined the mental health of older adults with DSL. In accordance with the Preferred Reporting Items for Systematic Reviews (PRISMA) statement, specific databases were searched and eight articles were selected for final review. Seven studies investigated the association between DSL and depression or depressive symptoms, whilst one study explored the relationship between DSL and quality of life. No studies investigated the impact of DSL on anxiety. Overall, results of this review suggested that there is a significant relationship between DSL and decreased mental health with those with DSL either displaying depressive symptoms or being at risk for developing depression. Future research should focus on comparative studies of older people with and without sensory loss, as well as targeted studies of older people with dual sensory loss, that incorporate well-defined and valid measures of sensory loss and mental health.